Disclosing gen Z’s perception on cultural diplomacy practices in digital media through the role of Korean celebrities in Indonesian products - Fatma Dian Pratiwi; Maya Sandra Rosita Dewi; Rahmah Attaymini; Rama Kerta Mukti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
This article disclose how generation Z’s perception toward digital culture diplomacy practice manifests in the assigning of Korean celebrities in Indonesian products’ brand. This is related with how they interest into Korean culture. This is following the entry of the Korean wave of culture into Indonesia, particularly through digital media such as social media, drama, fashion, music, and tourism. Since cultural diplomacy is not only limited to cultural exchanges sponsored by the Government or the State and carried out directly. In the digital era, cultural diplomacy is carried out by digital media and can be carried out by non-government actor use as brand ambassador for products such as foods, beauty products, fashion and so forth. This research uses a qualitative approach with the Case Study method. While the analysis is carried out using the VisCap model analysis which includes Visibility, Credibility, Attractiveness, and Power. These four aspects are then analyzing within the framework of cultural diplomacy in the digital era. The results of this study explain that the current culture of diplomacy is carried out in a way called soft powers. One of them is by how Indonesia uses Korean celebrities as brand ambassadors for their local brand. The reason for choosing is due to the celebrity's popularity, credibility, attractiveness, and power, which also boosts the products offered and establish attention. The relations between using Korean celebrities as brand ambassadors is certainly felt by Korea and Indonesia, which previously had been well established in diplomatic relationships.